Sustaining good perceptions towards recipients of zakat under the category of riqab - Ismail, Yusof; Awang, Abdul Bari; Mhd. Sarif, Suhaimi (2019)
Sustaining good perceptions is essential. Riqab (slavery) is one of the standard categories of zakat expenditure sanctioned by Islam. Today, it is difficult if not impossible to identify people who may be entitled to zakat under riqab category. However, Fiqh literature has provided some novel ideas of practical implications to contemporary Muslim societies. This study aims to explore the views of some Muslim respondents on the perception of zakat recipients under riqab category. By using nine statements with a Likert-like scale, and one open-ended question, the study was able to obtain an acceptable reliability (Cronbach reliability of 0.704). Data analysis using t-test shows that male and female respondents (n=70) did not differ significantly in their views, except for “freeing a prisoner of war” (p-value .002). The rating by the respondents on eligible riqab recipients ranked “freeing a person from an oppressive ruler” (4.09/5.00), and “freeing a prisoner of war” (4,03/5.00) among the top. A significant contribution of the research is perhaps the development of the instrument which may be replicated on other types of respondents.